Peningkatan Ketahanan Keluarga Melalui Optimalisasi Program Pemerintah - M. Bahtiar Ubaidillah; Ragil Ira Mayasari; Ahmad Khamim Tohari; Laily Lailatul Fatma Rozyah; Akhmad Imam Muttakin; Laili Zamalikha; Christian Davi Kurniawan; Clarisa Herda Falevy; Vicky Vidiana Vici; Achmad Denny Nur Sanjaya; Adi Arif Wibowo; Amy Fatona; Arga Verdianto Muhamad; Deni Irawan; Denny Sukma Tri Prihatno; Dian Purna Irawan; Muhammad Dedy Alensa; Ullun Farohmah; Divania Sherylla Putri; Tofan Ade Irawan; Dwika Bagus Rusdyan Nugraha; Diah Ayu Widoretno; Leni Dwi Alfiana; Yesie Santa Charera (Politeknik Kampar, 2023)
A prosperous family is a family that is formed based on a valid marriage, and that meets the spiritual and material needs of a decent life, has harmonious and harmonious, balanced relationships between family members and society and the environment. To improve family quality, there are 5 pillars in indicators of family resilience and welfare that must be met, namely indicators of legality, integrity and gender equality, physical resilience, economic resilience, psychological resilience, and socio-cultural resilience. Through the Unimas Village T/A 2023/2024 Thematic Science KKN program, group 3 seeks to provide education and optimize programs carried out by the government as an effort to increase family resilience. The programs that we are optimizing include the introduction of recycling used materials to create a clean and productive environment, besides that it can improve the family economy. Socialization regarding the impact of early marriage and reducing stunting rates. Socialization raises awareness of the law of criminal acts in the household and deviant behavior. Through these socialization activities, the aim is to foster understanding, awareness and discipline in following and implementing existing government programs. It is hoped that with understanding, discipline and community participation in government programs, stable and prosperous family resilience will be created.